Capture and electroreduction of CO2 using highly efficient bimetallic Pd–Ag aerogels paired with carbon nanotubes. Issue 21 (24th May 2021) - Abdinejad, Maryam; Ferrag, Celia; Hossain, M. Nur; Noroozifar, Meissam; Kerman, Kagan; Kraatz, Heinz Bernhard
Abstract : Highly efficient three-dimensional palladium–silver aerogels for electrochemical reduction of CO2 to CO. Abstract : The rational design of efficient catalysts for electrochemical CO2 reduction is a critical step towards achieving industry-ready electrolyzer systems. Noble metal aerogels have emerged as state-of-the-art catalysts that play a crucial role in several applications. Here, we report bimetallic Pd x Ag y aerogels that have been optimized by modulating the Pd/Ag ratio for the capture and selective electroreduction of CO2 . Pd0.67 Ag0.33 exhibited the greatest ability to reduce CO2 to CO with faradaic efficiency (FE): 84% and current density ( j ): −23 mA cm −2 at −0.8 V vs. RHE in 0.1 M NaHCO3 . Using a carbon nanotube solid support (Pd0.67 Ag0.33 /CNT), we could further enhance the FE to 91% with a higher current density of −38 mA cm −2 at lower overpotential (−0.7 V vs. RHE). This remarkable catalytic activity is higher than that of monometallic Pd (FE: 43%, j : −3.4 mA cm −2 ) and Ag (FE: 68%, j : −2.6 mA cm −2 ) aerogels at −0.8 V vs. RHE. Using bimetallic aerogels provides an effective strategy that could inspire the design of new catalysts for a variety of applications.